Meningkatkan Efektivitas Pendidikan Agama Islam (PAI) Melalui Implementasi Kurikulum yang Berdaya Saing - Pebru Alim Tufando; Nurfuadi (Jurnal Dirosah Islamiyah, 2024)
Islamic Education has a very important role in shaping the character, morality and spiritual values ​​of Muslim individuals. In facing modern-day challenges, implementing a competitive curriculum is very important to ensure that Islamic Education provides optimal benefits. A competitive curriculum must be able to combine Islamic religious values ​​with contemporary educational needs and provide a comprehensive understanding to students. This article aims to explore various strategies and approaches to increase the effectiveness of Islamic religious education through the implementation of a competitive curriculum. Through a literature study approach, we present an in-depth review of concepts, challenges and solutions that can be applied in the context of Islamic religious education. We conclude that the implementation of a competitive curriculum in Islamic education has great potential to improve the quality of education, prepare students to face the challenges of the times, and form a generation of quality Muslims. Thus, this article provides comprehensive and in-depth insight into the importance of implementing a competitive curriculum in the context of Islamic religious education.